Electrolyte for lithium metal batteries and lithium metal battery comprising said electrolyte

CN122931032APending Publication Date: 2026-10-16HYUNDAI MOTOR CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511807633.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-03
Filing Date
2025-12-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

枝晶锂会导致电池内部发生电气短路,从而引发安全问题(例如电池着火等)

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931032A_ABST
    Figure CN122931032A_ABST
Patent Text Reader

Abstract

The present invention provides an electrolyte for a lithium metal battery and a lithium metal battery comprising the same, the electrolyte comprising a lithium salt, a non-aqueous organic solvent, and an additive. The additive comprises a compound represented by Chemical Formula 1 (R 1 -O-R 2 ) or Chemical Formula 1A. In Chemical Formula 1, R 1 is a substituted or unsubstituted C1 to C20 alkyl, R 2 is represented by the following Chemical Formula 2. In Chemical Formula 2, R ` and R`` are each independently a substituted or unsubstituted C1 to C20 alkyl, and * represents a moiety connected to one or more same or different atoms or chemical formulas. R 1 and R 2 are different from each other.[Chemical Formula 1A][Chemical Formula 2]
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Cross-references to related applications This application claims priority and benefit to Korean Patent Application No. 10-2025-0043333, filed with the Korean Intellectual Property Office on April 3, 2025, the entire contents of which are incorporated herein by reference. Technical Field

[0002] The present invention relates to an electrolyte for lithium metal batteries and a lithium metal battery comprising said electrolyte. Background Technology

[0003] With the growth of the electric vehicle market, the demand for high-capacity batteries exceeding lithium-ion batteries is increasing. Consequently, the demand for anode and cathode materials with high energy density and long-term stability for lithium metal batteries is also growing.

[0004] Lithium metal (with its high specific capacity of 3860 mAh / g and low standard electrode potential (i.e., -3.04 V relative to a conventional or standard hydrogen electrode)) has attracted considerable attention as a negative electrode material for rechargeable lithium-ion batteries. However, lithium metal is highly reactive and generates an extremely reducing atmosphere during charging, which can lead to irreversible decomposition reactions between the lithium metal and the electrolyte. These decomposition reactions can deplete the electrolyte, and the decomposition products can form a non-uniform film on the lithium metal surface. Furthermore, with repeated charging and discharging, lithium can grow in the form of dendrites. Dendritic lithium can cause electrical short circuits inside the battery, leading to safety issues such as battery fires. Summary of the Invention

[0005] In view of the above, in order to apply lithium metal with high stability and high capacity, it is necessary to develop an electrolyte that reduces the reactivity of lithium metal, prevents the growth of dendritic lithium, and enables uniform lithium deposition (coating).

[0006] One aspect provides an electrolyte for lithium metal batteries that can assist the function of an N,N-dimethylaminosulfonyl fluoride solvent in forming a negative electrode film, while significantly improving the durability and electrochemical characteristics of the lithium metal battery.

[0007] The electrolyte for lithium metal batteries according to the embodiment comprises a lithium salt, a non-aqueous organic solvent, and an additive, said additive comprising a compound of chemical formula 1 (R 1 -OR 2 Compounds represented by chemical formula 1A: [Chemical Formula 1A] .

[0008] In chemical formula 1, R 1R is a substituted or unsubstituted C1 to C20 alkyl group. 2 Represented by chemical formula 2: .

[0009] In chemical formula 2, R ` R and R`` are each independently a substituted or unsubstituted C1 to C20 alkyl group, and * indicates a portion connected to one or more identical or different atoms or chemical formulas.

[0010] In chemical formula 1, R 1 and R 2 They are different from each other.

[0011] In chemical formula 1, R 1 It can be an unsubstituted C1 to C10 alkyl group.

[0012] Non-aqueous organic solvents may contain N,N-dimethylaminosulfonyl fluoride.

[0013] Non-aqueous organic solvents may also contain viscosity reducers.

[0014] Viscosity reducers may contain compounds represented by chemical formula 3: .

[0015] In chemical formula 3, R 3 To R 6 Each can be an independent halogen group, and R 7 and R 8 Each can be an independent C1 to C20 alkyl group substituted or unsubstituted with one or more halogen groups.

[0016] Based on the total amount (100 wt%) of the electrolyte used in lithium metal batteries, additives containing compounds represented by chemical formula 1 may be included in amounts of "greater than 1.0 wt% and less than or equal to 2.0 wt%" or "1.5 wt% to 2.0 wt%".

[0017] The lithium salt may include at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), or lithium bis(trifluoromethylsulfonyl)imide (LiTFSI).

[0018] The concentration of the lithium salt can be in the range of 1.0 M to 4.0 M.

[0019] According to another embodiment of the present invention, a lithium metal battery may include: a positive electrode, a lithium metal layer facing the positive electrode as a negative electrode, a separator inserted between the positive electrode and the negative electrode, and an electrolyte for the lithium metal battery.

[0020] The electrolyte used in lithium metal batteries may be an electrolyte according to an embodiment of the present invention.

[0021] The thickness of the lithium metal layer can range from 5 μm to 50 μm.

[0022] The positive electrode may include lithium nickel manganese cobalt-based metal oxides. Attached Figure Description

[0023] Figure 1 Capacity-charge-discharge graph for evaluating the durability of lithium metal battery cells (button cells) containing electrolytes according to Example 1, Comparative Example 1, and Comparative Example 2.

[0024] Figure 2 Capacity-charge-discharge graph for evaluating the durability of lithium metal battery cells (button cells) containing electrolytes according to Example 2 and Comparative Example 3.

[0025] Figure 3 Scanning electron microscope (SEM) images of the morphology of lithium electrodeposited on the upper part of the lithium anode in a lithium metal battery cell (button cell) containing the electrolyte according to Comparative Example 1 after 10 charge / discharge cycles.

[0026] Figure 4 Scanning electron microscope (SEM) images of lithium electrodeposited on top of the lithium anode in a lithium metal battery cell (button cell) containing the electrolyte according to Comparative Example 2 after 10 charge / discharge cycles.

[0027] Figure 5 Scanning electron microscope (SEM) images of the morphology of lithium electrodeposited on the upper part of the lithium anode in a lithium metal battery cell (button cell) containing the electrolyte according to Example 1 after 10 charge / discharge cycles.

[0028] Figure 6 and Figure 7 Li, respectively, used for analyzing each electrolyte according to Example 1, Comparative Example 1, and Comparative Example 2. + With FSI - Between and FSI - Solvation structure with non-aqueous organic solvents (Li + ↔FSI - Raman analysis data of non-aqueous organic solvents.

[0029] Figure 8 Nuclear magnetic resonance (NMR) analysis data were used to quantitatively analyze the amount of lithium salt consumed during operation of lithium metal battery cells containing electrolytes according to Example 1, Comparative Example 1, and Comparative Example 2.

[0030] Figure 9 Capacity-charge-discharge graphs for evaluating the durability of lithium metal battery cells (button cells) containing electrolytes according to Examples 1 and 3-8.

[0031] Figure 10 A graph showing the ionic conductivity of each electrolyte according to Example 1, Comparative Example 1, and Comparative Example 2.

[0032] Figure 11 A graph showing the ionic conductivity of each electrolyte according to Examples 1 and 3-8. Detailed Implementation

[0033] In this invention, terms such as "first," "second," and "third" are used to describe various technologies, components, regions, layers, and / or portions, but are not limited thereto. These terms are used only to distinguish any component, assembly, region, layer, or portion from other components, assemblies, regions, layers, or portions. Therefore, without departing from the scope of this invention, the first component, assembly, region, layer, or portion described below may be referred to as the second component, assembly, region, layer, or portion.

[0034] The technical terms used herein are for the purpose of describing embodiments only and are not intended to limit the invention. Unless otherwise expressly stated otherwise, the singular forms used herein include the plural forms. The terms “comprising,” “having,” “including,” etc., as used in the specification, refer to specific features, regions, integers, steps, operations, elements, and / or components, and do not exclude other specific features, regions, integers, steps, operations, elements, and / or components.

[0035] When any part is referred to as being "on" or "above" other parts, that part may be directly on or above the other parts, or different parts may be involved between them. Conversely, when any part is referred to as "directly on" other parts, no other parts are inserted between them.

[0036] Unless otherwise defined, all terms used herein (including technical and scientific terms) shall have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. Unless otherwise defined, predefined terms of common use shall be further interpreted as having a meaning consistent with relevant technical literature and this invention, and shall not be construed as having an ideal or overly formal meaning.

[0037] As used herein, the term "combination thereof" as described in a Markush format expression means one or more mixtures or combinations of components selected from those described in the Markush format expression, and means including at least one of said components. In this invention, each phrase such as "A or B", "at least one of A and B", "at least one of A or B", "A, B or C", "at least one of A, B and C", "at least one of A, B or C", and "at least one of A, B or C or a combination thereof" may include any one or all possible combinations of the items listed in the corresponding phrase.

[0038] Additionally, as used herein, unless otherwise specifically defined, "*" refers to a part connected to the same or different atoms or chemical formulas.

[0039] In addition, as used herein, “Li-NCM” can refer to a lithium secondary battery (or lithium metal battery) that uses cathode active materials containing Ni, Co and Mn.

[0040] The invention will now be described more fully, with embodiments of the invention shown. Those skilled in the art will recognize that various modifications can be made to the described embodiments without departing from the spirit or scope of the invention.

[0041] Electrolytes for lithium metal batteries In lithium metal batteries, N,N-dimethylaminosulfonyl fluoride (DMSF or FSA)-based electrolytes undergo continuous oxidative and reductive decomposition. Therefore, there is a need for an additive composition that facilitates the formation of a solid electrolyte interphase (SEI) (negative electrode film) to minimize reactions between the electrolyte and the electrode. In fact, various additives are being developed to delay degradation, and this invention relates to a novel structural electrolyte additive for lithium metal batteries that achieves improved high durability performance.

[0042] Typically, N,N-dimethylaminosulfonyl fluoride (DMSF or FSA) is widely used as an electrolyte in lithium metal batteries to form a stable negative electrode film. In this example, compositions using the fluorinated solvent TTE (1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether) with a symmetrical structure as an ether electrolyte additive are known. It has been evaluated that this compensates for the disadvantages of high-concentration electrolytes by reducing the viscosity of the electrolyte, which has low viscosity characteristics, while maintaining the solvation structure of the electrolyte, which has extremely low lithium salt solubility due to the large number of -F functional groups (where F is fluorine). However, the problem of decreased durability due to the low electrochemical stability of the electrolyte has not yet been solved. One aspect of the present invention provides a novel asymmetric structure fluorinated additive that has never been proposed before. According to one aspect of the present invention, the novel asymmetric structure fluorinated additive is used in N,N-dimethylaminosulfonyl fluoride (hereinafter DMSF or FSA) series electrolyte-based lithium metal batteries, thereby simultaneously achieving the effects of reducing viscosity and improving durability.

[0043] The present invention provides an electrolyte composition that, by adding a novel asymmetric fluorinated additive, can delay electrolyte decomposition and help improve the durability of lithium metal batteries, and is advantageous whether added to DMSF series electrolytes or other fluorinated solvent series electrolytes.

[0044] The electrolyte for lithium metal batteries according to the embodiment may comprise a lithium salt, a non-aqueous organic solvent, and an additive, said additive comprising a component of chemical formula 1 (R 1 -OR 2 Compounds represented by chemical formula 1A: [Chemical Formula 1A] .

[0045] In chemical formula 1, R 1 R is a substituted or unsubstituted C1 to C20 alkyl group. 2 Represented by chemical formula 2: .

[0046] In chemical formula 1, R 1 and R 2 They are different from each other.

[0047] In formula 2, R` and R`` are each independently a substituted or unsubstituted C1 to C20 alkyl group, and * indicates a portion connected to one or more identical or different atoms or chemical formulas.

[0048] In chemical formula 2, R ` R and R'' are each independently trifluoromethyl.

[0049] Based on the structure of the compound represented by chemical formula 1, R 1 and R 2 The substituents are located on both sides of the *-O-CH2-* linking group. As mentioned above, due to R 1 and R 2 They are different from each other, therefore the compounds represented by chemical formula 1 have asymmetrical structures.

[0050] In other words, in chemical formula 1, R 1 It is not represented by chemical formula 2.

[0051] For example, in chemical formula 1, R 1 It can be an unsubstituted C1 to C10 alkyl group. In this example, the improvement in the durability performance of the lithium metal battery according to the embodiment can be maximized or enhanced.

[0052] Based on the total amount (100 wt%) of the electrolyte for lithium metal batteries, an additive containing a compound represented by chemical formula 1 can be included in an amount greater than 0.1 wt% and less than or equal to 2.0 wt%. By controlling the amount of additive as described above, the formed SEI film will not be too thin or too thick, and the inherent solvation structure of the electrolyte will not be altered by the additive, thereby significantly improving the durability characteristics of the lithium metal battery containing the additive.

[0053] Based on the total amount (100 wt%) of the electrolyte used in lithium metal batteries, additives containing compounds represented by Formula 1 may be included in amounts ranging from 0.5 wt% to 2.0 wt%, for example, from 1.5 wt% to 2.0 wt% (or 1.5 wt% in another example). When the electrolyte (e.g., an electrolyte in a non-aqueous organic solvent without the viscosity reducer described below) is composed of additives containing compounds represented by Formula 1 within the above range, the cycle life characteristics of the lithium metal battery, including the lithium metal anode, can be improved, and it can exhibit very stable coulombic efficiency.

[0054] Non-aqueous organic solvents may include N,N-dimethylaminosulfonyl fluoride (DMSF or FSA). These types of non-aqueous organic solvents exhibit high compatibility with lithium metal anodes and excellent compatibility with lithium salts containing fluorosulfonyl groups. Therefore, when used as solvents to synthesize electrolytes with the composition according to the embodiments, the SEI interface characteristics of lithium metal can be improved, and durability performance can be significantly enhanced.

[0055] In addition to the types mentioned above, non-aqueous organic solvents may also include ether solvents, or ether solvents may be used alone as non-aqueous organic solvents. Ether solvents may include dipropyl ether, dimethoxy ether, diethyl ether, 1,2-diethoxyethane, cyclopentylmethyl ether, methylpropyl ether, n-butylmethyl ether, ethylpropyl ether, dimethoxymethane, 1,4-dioxane, 1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, or combinations thereof.

[0056] Non-aqueous organic solvents may also contain viscosity reducers.

[0057] For example, viscosity reducers may include compounds represented by chemical formula 3: .

[0058] In chemical formula 3, R 3 To R 6 Each is an independent halogen group, R 7 and R 8 Each is independently a C1 to C20 alkyl group that is substituted or unsubstituted with one or more halogen groups.

[0059] For example, in R 3 To R 8 In this context, the halogen group can be a fluorine group (*-F).

[0060] For example, a compound represented by chemical formula 3 can also be represented by chemical formula 3-1: .

[0061] Electrolytes developed to date for lithium metal batteries exhibit high viscosity due to their composition involving the dissociation of high-concentration salts. Therefore, viscosity reducers are needed to improve the low wettability of the electrolyte at the positive electrode. Through repeated studies of the structure of suitable viscosity reducers, this invention has demonstrated that when using viscosity reducers having a structure represented by Chemical Formula 3 (particularly Chemical Formula 3-1), the viscosity of the electrolyte can be reduced while simultaneously improving the durability of the lithium metal battery.

[0062] For example, when a viscosity reducer is included in the non-aqueous organic solvent in the electrolyte for a lithium metal battery according to the embodiment, it is advantageous to include an additive containing a compound represented by chemical formula 1 in an amount of 1.5% to 2.0% (e.g., 2.0% by weight) based on the total amount (100% by weight) of the electrolyte for the lithium metal battery, thereby reducing the viscosity of the electrolyte while maximizing the durability performance of the lithium metal battery.

[0063] According to the implementation scheme, the lithium salt may include at least one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide (LiFNFSI), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), or lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), for example, it may be LiFSI.

[0064] The concentration of lithium salt contained in the electrolyte for lithium metal batteries according to the implementation scheme can be from 1.0 M to 4.0 M, for example, from 1.0 M to 3.5 M, 1.0 M to 3.0 M, 1.0 M to 2.5 M, 1.0 M to 2.0 M, or 1.0 M to 1.5 M.

[0065] If the lithium salt concentration is below the aforementioned range, the electrolyte conductivity may decrease, potentially leading to poor electrolyte performance. Conversely, if the lithium salt concentration exceeds the aforementioned range, the electrolyte viscosity may increase, potentially resulting in reduced lithium-ion mobility and overvoltage issues at the start of cycling. Furthermore, it is detrimental that the SEI layer formed on the surface of the lithium metal (which is the negative electrode) may not form at all or may form an excessively thick film, which could reduce the electrochemical performance of the lithium metal battery.

[0066] Lithium metal batteries Another embodiment provides a lithium metal battery comprising an electrolyte for lithium metal batteries as described above.

[0067] A lithium metal battery may include a positive electrode, a lithium metal layer facing the positive electrode as a negative electrode, a separator inserted between the positive and negative electrodes, and an electrolyte for the lithium metal battery.

[0068] The negative electrode for lithium metal batteries can be a lithium metal layer, and the lithium metal layer itself can be used as the negative electrode of the battery.

[0069] During charging, the battery, including the negative electrode, allows lithium ions to move from the positive to the negative electrode, thus forming a lithium metal layer. Charging and discharging of the battery can be performed by forming or removing this lithium metal layer.

[0070] The negative electrode can be formed or arranged on the negative current collector (e.g., copper).

[0071] A lithium metal layer can be formed on the negative electrode current collector through the charging and discharging of a lithium metal battery.

[0072] The thickness of the lithium metal layer can be from 5 μm to 50 μm, for example, from 10 μm to 50 μm, or it can be formed to have the above thickness.

[0073] When the lithium metal layer meets the above thickness, side reactions between the lithium metal layer and the electrolyte can be suppressed, thereby improving the electrochemical performance of the lithium metal battery.

[0074] In another implementation, the positive and negative electrodes are arranged opposite each other.

[0075] The positive electrode may include a positive current collector and a layer of positive active material formed on the positive current collector.

[0076] The positive current collector can be made of stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel with surface treatment using carbon, nickel, titanium, silver, etc.

[0077] The thickness of the positive current collector can range from 3 μm to 500 μm.

[0078] The positive electrode active material layer contains positive electrode active material.

[0079] The positive electrode active material can be a compound capable of lithium insertion and extraction (i.e., lithium insertion and extraction), and specifically can include lithium iron phosphate. When the positive electrode active material includes lithium iron phosphate, the compatibility with the electrolyte is optimal or significantly improved, thereby maximizing or enhancing the effect of improving battery performance.

[0080] The positive electrode active material may include lithium metal oxide, which is a compound capable of inserting and deintercalating lithium, and is, for example, a lithium metal oxide containing at least one of cobalt, manganese, nickel, or aluminum. For example, the lithium metal oxide may include at least one of lithium manganese-based oxide, lithium cobalt-based oxide, lithium nickel-based oxide, lithium nickel manganese-based oxide, lithium nickel cobalt-based oxide, lithium manganese cobalt-based oxide, lithium manganese cobalt-based oxide, or lithium nickel cobalt transition metal (M) oxide.

[0081] The positive electrode active material can be a lithium nickel manganese cobalt-based oxide, which can improve the battery's capacity characteristics and stability. The positive electrode active material can be represented by chemical formula 4: Li(Ni x Co y Mn z )O2.

[0082] In chemical formula 4, Li represents lithium, Ni represents nickel, Co represents cobalt, Mn represents manganese, O represents oxygen, 0≤x≤1, 0≤y≤1, 0≤z≤1, and x+y+z=1.

[0083] For example, in chemical formula 4, 0.8≤x≤1, 0≤y≤1, 0≤z≤1, and x+y+z=1.

[0084] For example, in chemical formula 4, 0.89≤x≤1, 0≤y≤1, 0≤z≤1, and x+y+z=1.

[0085] In other words, the positive electrode can contain positive electrode active materials including lithium nickel manganese cobalt-based metal oxides.

[0086] The positive electrode active material layer may also contain adhesives and / or conductive materials.

[0087] The separator separates the negative and positive electrodes and provides a channel for the movement of lithium ions. There are no restrictions on the type of separator used in rechargeable lithium batteries.

[0088] The following embodiments illustrate the present invention in more detail. However, the following embodiments are merely implementations of the present invention, and the present invention is not limited to the following embodiments.

[0089] Example - Preparation of electrolyte for lithium metal batteries After adding 1 M LiFSI salt to the FSA solvent and dissociating it to form an electrolyte, an additive (the amount of which is obtained by weight ratio) is added to the dehydrated electrolyte and dissociated. Then, calcium hydride (CaH2) is added at 1% or more of the total sample weight, and the mixture is removed after 30 minutes, thus finally preparing the electrolyte for lithium metal batteries. Each electrolyte of Example 2 and Comparative Example 3 was prepared by using an FSA solvent containing a viscosity reducer represented by Chemical Formula 3-1 instead of the aforementioned FSA solvent.

[0090] Table 1 shows the composition of the electrolyte for lithium metal batteries according to the embodiments and comparative embodiments.

[0091] In Table 1, the amount of additives is based on the total amount of each electrolyte.

[0092] Table 1 Chemical formula E-1: Chemical formula C-1: Chemical formula C-2: Experimental Examples 1. Electrochemical evaluation of Li-NCM Li-NCM Durability: The durability and electrochemical properties of each electrolyte were evaluated in the same battery structure using a 20 μm thick lithium film as the anode and NCM as the cathode.

[0093] Li-NCM electrodeposition morphology: Using a 20 μm thick thin film of lithium as the negative electrode and NCM as the positive electrode, the battery was operated through predetermined cycles and then charged and disassembled to examine the lithium electrodeposition morphology on the cross section and top.

[0094] 2. Raman solvation structural analysis and quantitative analysis of degradation trends by nuclear magnetic resonance (NMR) Raman analysis: Analyze 3 mL of each electrolyte sample using the Raman evaluation kit for liquid samples under conditions without exposure to the external atmosphere.

[0095] NMR analysis: The lithium salt consumption trend was quantitatively analyzed by using 500 MHz to quantitatively analyze the remaining amount of lithium salt and solvent in each battery operating cycle.

[0096] 3. Evaluation of electrolyte performance Ionic conductivity: The ionic conductivity (mS / cm, at room temperature) of each electrolyte prepared at room temperature was evaluated using an ionic conductivity meter.

[0097] The evaluation results of Experiment Examples 1-3 are shown below.

[0098] Evaluation 1: Evaluating the durability of lithium metal batteries based on additive type. The additive represented by chemical formula E-1 was compared and evaluated by selecting comparative additive materials with similar molecular structures to verify its effect on improving the durability of lithium metal batteries. Specifically, the additive represented by chemical formula E-1 (Example 1) and the additive represented by chemical formula C-1 with a similar molecular structure (Comparative Example 2) were added to the electrolyte according to Comparative Example 1, and the electrochemical characteristics were evaluated based on their differences. The results are as follows: Figure 1 As shown.

[0099] refer to Figure 1 Unlike lithium metal battery cells containing the electrolyte according to Comparative Example 1, lithium metal battery cells containing the electrolyte according to Example 1 were found to exhibit improved durability after 80 cycles. Figure 1 A graph showing the percentage of capacity retention is presented, which represents the ratio of the discharge capacity of each cycle to the discharge capacity of the initial cycle. The decrease in discharge capacity in the second half of the cycle indicates battery degradation caused by lithium salt consumption in the electrolyte, solvent decomposition, etc.

[0100] Additionally, refer to Figure 1Compared to lithium metal battery cells containing the electrolyte according to Comparative Example 1 and lithium metal battery cells containing the electrolyte according to Example 1, lithium metal battery cells containing the electrolyte according to Comparative Example 2 (which contains an additive having a structure similar to that of Example 1) exhibit considerably lower durability performance. Therefore, the durability improvement effect of the additive material represented by Chemical Formula E-1 is caused by a fluorinated solvent having a simple asymmetric structure and is influenced by the type of *-CF3 functional group having a terminal *-F functional group and the amount of F.

[0101] Evaluation 2: Durability evaluation when viscosity reducers are included Unlike general electrolytes used in lithium-ion batteries, electrolytes developed to date for lithium metal batteries exhibit high viscosity due to their composition involving dissociation from high-concentration salts. Therefore, additive development should focus on the characteristics of additives for lithium metal batteries in electrolyte compositions that include viscosity reducers in addition to conventional solvents, and in electrolyte compositions using only conventional solvents. Thus, embodiments of the present invention aim to verify the effect of compositions containing viscosity reducers on improving battery characteristics. That is, since viscosity reducers must be used to reduce the viscosity of high-concentration electrolytes, the combination of additive materials represented by chemical formula E-1 with viscosity reducers is evaluated relative to the durability improvement effect as a performance improvement effect, and the results are as follows: Figure 2 As shown (Lithium metal battery (button cell) durability evaluation; 1 / 3 C durability evaluation using a 20 μm Li thin film).

[0102] refer to Figure 2 As an evaluation of the durability of the additive represented by chemical formula E-1 in an electrolyte composition containing an FSA main solvent and a co-solvent (viscosity reducer) represented by chemical formula 3-1, the additive represented by chemical formula E-1 exhibited improved durability performance, while the additive material represented by chemical formula C-2 exhibited considerably lower durability performance. Therefore, the combination of the additive represented by chemical formula E-1 and the viscosity reducer represented by chemical formula 3-1 confirmed the improved durability performance.

[0103] Evaluation 3: Analysis of lithium-ion battery cell deposition morphology based on additive type To verify the role of the compound represented by chemical formula E-1 (a film-forming additive), the battery was subjected to 10 charge-discharge cycles. The morphology of lithium electrodeposited on top of the wound lithium was then observed using the same Li-NCM coin cell evaluation tool after the lithium ions migrated from the positive NCM to the lithium negative electrode. In lithium metal battery (LMB) cells, the electrodeposition of lithium ions migrating from the positive to the negative electrode is a crucial factor directly related to the durability performance of the LMB.

[0104] refer to Figures 3 to 5When additives represented by chemical formula E-1 and chemical formula C-1 are applied respectively, the batteries initially operate with similar performance, with no particular degradation for each material.

[0105] Evaluation 4: Raman analysis of the solvation structure of each electrolyte. Electrolytes possess a stable solvation structure resulting from the interactions of the lithium salt, solvent, additives, and co-solvent (viscosity reducer) that constitute the electrolyte. This solvation structure influences the electrochemical decomposition tendency, decomposition products, and electrode stability of each electrolyte component. Therefore, understanding the solvation structure of the electrolyte is crucial for determining the electrochemical properties of the battery, and it is necessary to verify how the application of additives alters this structure.

[0106] refer to Figure 6 and Figure 7 The results of Example 1 (where an additive represented by chemical formula E-1) and Comparative Example 1 (where no additive was used) show that they have the same solvation structure, which confirms that the additive represented by chemical formula E-1 does not interfere with the unique solvation structure of the electrolyte itself. This also means that the additive does not increase the viscosity of the electrolyte, and when combined with viscosity reducers, durability performance can be further maximized.

[0107] In addition, refer to Figure 6 and Figure 7 The electrolyte solvation structure was compared with that of Comparative Example 1 and Comparative Example 2, with or without the presence of an additive represented by chemical formula C-1. The Raman shift was 750 cm⁻¹. -1 and 725 cm -1 The decreased intensity of the nearby peaks corresponding to AGG and CIP indicates a change in the solvation structure. The AGG and CIP peaks suggest that Li + With FSI - The binding state between them (Li) + ↔FSI - (Among them, the higher the AGG ratio, the better the durability, because it is determined by FSI) - (Bis(fluorosulfonyl)imide) decomposes to form LIF (lithium fluoride)-based inorganic SEI. AGG is an abbreviation for aggregate (or aggregated ion cluster), and CIP is an abbreviation for contact ion pair. AGG refers to the state in which multiple ions (mainly lithium ions and anions) are combined (a single Li...). + Ions in clusters with multiple FSIs - The ion-bonded state, or multiple Li + Ions in clusters with multiple FSIs - The state of ion bonding), while CIP refers to the structure in which lithium ions and anions directly contact each other to form a pair (Li). + Ions and FSI- (The ions are directly bound in a 1:1 ratio). In Raman spectroscopy, these two structures are distinguished by different peaks and can be used to quantitatively analyze changes in the dissolved structure.

[0108] Evaluation 5: NMR analysis used for quantitative analysis of lithium salt consumption of each electrolyte. In systems using lithium metal as the negative electrode and LiFSI-FSA as the lithium salt and solvent, the decomposition and consumption of the lithium salt and solvent (which are components of the electrolyte) lead to electrolyte consumption (a degradation factor of lithium metal batteries). Electrolyte consumption can result in decreased lithium-ion conductivity due to the gradual decrease in electrolyte concentration, deterioration of output characteristics, and battery short circuits due to uneven lithium deposition, thereby shortening battery life. Therefore, to evaluate the effect of improving the characteristics of the lithium metal battery according to the embodiment, the remaining FSI and FSA in the electrolyte after the lithium metal battery has been operated were quantitatively analyzed by removing the electrolyte, and the results are as follows: Figure 8 As shown.

[0109] refer to Figure 8 As a result of quantitative analysis of the amounts of FSA and FSI of the electrolytes after the 50th and 100th cycles of battery operation for each electrolyte, it was found that the residual amount of each component in Example 1 was greater than that in Comparative Example 2. In other words, by comparing Example 2 and Example 1, the improvement effect of the additive represented by chemical formula E-1 was compared and demonstrated, wherein even when using the same asymmetric fluorinated solvent structure, the battery improvement effect varies depending on the number and branching shape of the *-F functional groups.

[0110] Evaluation 6: Quantitative evaluation of the electrochemical properties of lithium metal battery cells to determine the optimal dosage. To evaluate the lithium metal battery characteristics at the optimal amount of the additive represented by chemical formula E-1, the durability of the lithium metal battery cell was evaluated by adding the additive having the described structure in amounts ranging from 0.1 wt% to 5.0 wt%, and the results are as follows: Figure 9 As shown (Lithium metal battery durability evaluation; coin cell; 1 / 3 C durability evaluation using 20 μm thin film Li).

[0111] refer to Figure 9 When 1.5% by weight of the additive represented by chemical formula E-1 (Example 1) was used, the battery durability was greatly improved; however, in particular, Examples 6-8 (where more than 1.5% by weight of the additive was used) showed almost no improvement in durability. In this way, it is confirmed that the difference in durability improvement effect based on the amount of additive is mainly caused by the following two factors: i) SEI film thickness: When additives make the SEI film too thick, it becomes a source of battery resistance; and ii) Electrolyte solvation structure: When too many additives are included, the additives themselves can change the inherent solvation structure of the electrolyte, which may limit the film formation effect.

[0112] Therefore, the fluorinated solvent-based additive represented by chemical formula E-1 has the best durability improvement effect according to its amount, and when used in an electrolyte composition without viscosity reducer, the optimal amount of additive for improving durability performance is 1.5 by weight based on the total amount of electrolyte.

[0113] Evaluation 7: Analysis of electrolyte ionic conductivity at room temperature The electrolyte ionic conductivity of the electrolytes in Examples 1-8 and Comparative Examples 1-3 was analyzed at room temperature (20°C), and the results are shown in... Figure 10 and Figure 11 middle.

[0114] refer to Figure 10 and Figure 11 As a result of analyzing the ionic conductivity based on the type and amount of additives, all electrolytes exhibited a similar ionic conductivity of approximately 3.8 mS / cm, which confirms that the additive represented by the chemical formula E-1 simultaneously plays a role in forming the negative electrode film while maintaining the lithium-ion transport characteristics of the electrolyte.

[0115] Furthermore, despite similar ionic conductivity, the electrolyte of Example 1 exhibited significantly different durability characteristics compared to the other components, confirming that the improvement effect of the additive represented by chemical formula E-1 is due to the negative electrode film-forming effect of the bulk electrolyte rather than its ion transport characteristics.

[0116] One aspect of the present invention provides a lithium metal battery electrolyte that exhibits improved electrochemical properties by comprising additives for forming an asymmetric fluorinated solvent-based negative electrode film. Lithium metal batteries suffer from problems requiring improvement, such as lithium growth in a dendritic form, continuous redox decomposition reactions in the electrolyte and electrodes, and capacity degradation due to irreversible lithium generation during charging / discharging. The present invention has demonstrated that, in order to improve the durability of lithium metal batteries, additives according to the embodiments can be strategically used to form a stable thin film (LIF-based SEI) on the negative electrode, thereby improving electrochemical properties, thus achieving the present invention.

[0117] As mentioned earlier, existing technologies have only reported the use of fluorinated solvents (with *-F functional groups and symmetrical aliphatic chain structures) (e.g., TTE) as electrolytes to improve the electrochemical characteristics of lithium metal batteries through the formation of inorganic SEI by the fluorinated solvent. The significance of this technology lies in the fact that by adding *-F functional groups to the aliphatic chains of materials with ether functional groups to induce the formation of *-F functional group-based SEIs and by adjusting the molecular structure of the additive material itself, the electrochemical characteristics of lithium metal batteries can be achieved. However, to date, only the properties of fluorinated solvents with aliphatic chain structures symmetrically located on both sides of the ether functional groups have been reported; the role of additives in fluorinated solvents with asymmetrical structures has not yet been reported.

[0118] The present invention differs from existing technologies in that it synthesizes a novel fluorinated solvent material with an asymmetric structure and applies it as an additive to electrolytes used in lithium metal batteries, thereby improving durability and electrochemical properties. This points to a new direction for the development of additives for lithium metal batteries. In particular, since the additive effect of asymmetric fluorinated solvents has not yet been applied and verified in FSA (dimethylaminosulfonyl fluoride) solvent-based electrolytes (which are currently known to be stably used as the main solvent in lithium metal batteries), the electrolyte according to embodiments of the present invention and the lithium metal battery containing said electrolyte may differ from existing technologies in terms of composition and performance.

[0119] More specifically, as examined in the above evaluation, the original molecular structure of the additive material is the main factor determining the reduction and decomposition tendency of the additive used to generate inorganic material-based SEIs, wherein the decomposition tendency and SEI products vary with the functional groups of the additive molecule, which is crucial to the effect of the additive. This invention provides an additive for forming a negative electrode film in an FSA solvent, which has the following three differentiating factors (i.e., the structure of the compound represented by Chemical Formula 1), thereby improving the electrochemical characteristics of lithium metal batteries and exploring the improvement effect: a. Introduce *-F functional groups for generating LIFs; b. Application of ether-based asymmetric aliphatic chain structures; and c. The number of *-F functional groups and the type of aliphatic chain.

[0120] An electrolyte for lithium metal batteries according to an embodiment of the present invention comprises an asymmetric fluorination additive for a fluorinated solvent, said asymmetric fluorination additive being able to replace TTE (which is a well-known conventional fluorinated solvent for lithium metal batteries) to generate a more stable LIF-based inorganic SEI, thereby improving battery durability.

[0121] The electrolyte for lithium metal batteries according to the embodiment includes additives with a specific structure that contribute to the formation of the negative electrode film, thus enabling the lithium metal battery containing the electrolyte to exhibit excellent durability performance. Furthermore, by further including a viscosity reducer with a specific structure as a non-aqueous organic solvent in the electrolyte, the durability performance of the lithium metal battery containing the viscosity reducer can be maximized or improved.

[0122] Although embodiments of the present invention have been described above, the present invention is not limited thereto, and various modifications can be made within the scope of the patent claims, the detailed description of the present invention, and the accompanying drawings, and these modifications also fall within the scope of the present invention.

[0123] Therefore, the scope of this invention is defined by the appended claims and their equivalents.

Claims

1. An electrolyte for lithium metal batteries, the electrolyte comprising: Lithium salts; Non-aqueous organic solvents; and Additives, said additives comprising compounds represented by chemical formula 1: R 1 -O-R 2 , in, In chemical formula 1, R 1 R is a substituted or unsubstituted C1 to C20 alkyl group. 2 Represented by chemical formula 2: , In chemical formula 2, R ` R and R'' are each independently a substituted or unsubstituted C1 to C20 alkyl group. * indicates a portion connected to one or more identical or different atoms or chemical formulas, and R 1 and R 2 They are different from each other.

2. The electrolyte for lithium metal batteries according to claim 1, wherein, R 1 It is an unsubstituted C1 to C10 alkyl group.

3. The electrolyte for lithium metal batteries according to claim 1, wherein, The non-aqueous organic solvent contains N,N-dimethylaminosulfonyl fluoride.

4. The electrolyte for lithium metal batteries according to claim 3, wherein, The non-aqueous organic solvent also contains a viscosity reducer.

5. The electrolyte for lithium metal batteries according to claim 4, wherein, The viscosity reducer comprises a compound represented by chemical formula 3: , In chemical formula 3, R 3 To R 6 Each is an independent halogen group, and R 7 and R 8 Each is independently a C1 to C20 alkyl group that is substituted or unsubstituted with one or more halogen groups.

6. The electrolyte for lithium metal batteries according to claim 4, wherein, Based on the total amount of electrolyte used in lithium metal batteries, an additive containing a compound represented by chemical formula 1 is included in an amount of 1.5% to 2.0% by weight.

7. The electrolyte for lithium metal batteries according to claim 1, wherein, Based on the total amount of electrolyte used in lithium metal batteries, an additive containing a compound represented by chemical formula 1 is included in an amount greater than 1.0% by weight and less than or equal to 2.0% by weight.

8. The electrolyte for lithium metal batteries according to claim 1, wherein, The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, or lithium bis(trifluoromethylsulfonyl)imide.

9. The electrolyte for lithium metal batteries according to claim 1, wherein, The concentration of the lithium salt is in the range of 1.0 M to 4.0 M.

10. A lithium metal battery, the lithium metal battery comprising: positive electrode; The lithium metal layer facing the positive electrode serves as the negative electrode; A diaphragm, the diaphragm being inserted between the positive electrode and the negative electrode; and Electrolytes used in lithium metal batteries in, The electrolyte comprises: Lithium salts Non-aqueous organic solvents, and Additives, said additives comprising compounds represented by chemical formula 1: R 1 -O-R 2 , In chemical formula 1, R 1 It is a substituted or unsubstituted C1 to C20 alkyl group. R 2 Represented by chemical formula 2: , In chemical formula 2, R ` R and R'' are each independently a substituted or unsubstituted C1 to C20 alkyl group. * indicates a portion connected to one or more identical or different atoms or chemical formulas, and R 1 and R 2 They are different from each other.

11. The lithium metal battery according to claim 10, wherein, The lithium metal layer is formed to have a thickness in the range of 5 μm to 50 μm.

12. The lithium metal battery according to claim 10, wherein, The positive electrode contains lithium nickel manganese cobalt-based metal oxide.

13. The lithium metal battery according to claim 10, wherein, R 1 It is an unsubstituted C1 to C10 alkyl group.

14. The lithium metal battery according to claim 10, wherein, The non-aqueous organic solvent contains N,N-dimethylaminosulfonyl fluoride.

15. The lithium metal battery according to claim 14, wherein, The non-aqueous organic solvent also contains a viscosity reducer.

16. The lithium metal battery according to claim 15, wherein, The viscosity reducer comprises a compound represented by chemical formula 3: , In chemical formula 3, R 3 To R 6 Each is an independent halogen group, and R 7 and R 8 Each is independently a C1 to C20 alkyl group that is substituted or unsubstituted with one or more halogen groups.

17. The lithium metal battery according to claim 15, wherein, Based on the total amount of electrolyte used in lithium metal batteries, an additive containing a compound represented by chemical formula 1 is included in an amount of 1.5% to 2.0% by weight.

18. The lithium metal battery according to claim 10, wherein, Based on the total amount of electrolyte used in lithium metal batteries, an additive containing a compound represented by chemical formula 1 is included in an amount greater than 1.0% by weight and less than or equal to 2.0% by weight.

19. The lithium metal battery according to claim 10, wherein, The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, or lithium bis(trifluoromethylsulfonyl)imide.

20. The lithium metal battery according to claim 10, wherein, The concentration of the lithium salt is in the range of 1.0 M to 4.0 M.

Citation Information

Patent Citations

  • Compounds, liquid crystal compositions and liquid crystal display elements, sensors, liquid crystal lenses, optical communication devices and antennas using the same

    KR1020250043333A